LITERACY AND HYPERACTIVITY IN EARLY EARLY EDUCATION - Maria da Silva, Berenice; Edjane da Silva Soares Guabira, Maria; José Brito da Silva, Maria; Gomes de Souza, Laudenice; Cândido Pereira, Edjanete; Farias Santos da Silva, Adriana; Maria da Silva, Josina; Berto Silva, Gledson; Edjanir Cândido Pereira, Maria; Margarete do Nascimento Mendonça, Maria (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to observe how literacy happens in hyperactive children in early childhood education. The term literacy has currently been used by some scholars to designate the process of developing reading and writing skills in social and professional practices. It is known that hyperactive children have concentration and learning difficulties. However, it needs attention so that literacy can occur in literacy activities. The understanding of the professional (teacher and psychologist) is essential to facilitate the understanding of reading and writing for students with ADHD (Attention Deficit Hyperactivity Disorder) or ADD (Attention Deficit Disorder). However, it is possible to deal with this group of students, work and interact with them. Because, their knowledge of the world prevails and provides them with reading and writing skills. Children with hyperactivity disorders need initiatives from teachers at school so that attention deficit problems can be overcome and teaching, learning and literacy can flow both in writing and reading and in social practice.